Marketing Channel Patterns And Marketing Costs Of Imported Buffalo Meat By Badan Urusan Logistik (Bulog) In Bandung City - Andreas Recki Prasetyo; Kurnia Khafidhatur (CV Putra Publisher, 2024)
This research was held at Badan Urusan Logistik (Bulog), PT. Yoga Mandiri Utama, retailers in the (Market) Ciroyom, Caringin, and Astana Anyar in January 2017 to February 2017. The aim of this research is to determine the pattern of the distribution channel and marketing costs of imported buffalo meat of Badan Urusan Logistik (Bulog) in Bandung City. The method of this research is case study. Analysis of data using analysis costs, margins, and profits. Based on the research, it is known that some distribution channel patterns are formed, channel one: Producer - Bulog - Consumers, channels two: Producer - Bulog - PT. Yoga Utama Mandiri - Consumer, channels three: Producer - Bulog - PT.Yoga Mandiri Utama - Wulandari's catering, channels four: Producer - Bulog - PT. Yoga Utama Mandiri - Supplier - Retailers - Consumer. Total costs incurred by each marketing channel patterns is channel one Rp10.670,00 per kilogram, channel two Rp2.840,00 per kilogram, channel three Rp3.740,00 per kilogram, and channel four Rp4.640,00 Rp per kilogram. The amount of profit earned by each of marketing pattern is channels one Rp330,00 per kilogram, channel two Rp Rp2.160,00 per kilogram, channel three Rp4.260,00 per kilogram, and channel four Rp6.360,00 per kilogram